Consumer Perceptions, Attitudes and Behavior towards Healthy Foods : The Case of Czech and Dutch Millennial Consumers - Van Wetten, Rick (2019)
A poor diet quality, poor health outcomes and obesity are examples of major health concerns across the world and a healthy diet has become a major topic of public discussion worldwide. The aim of this research paper is to analyze the differences in healthy foods perception and attitudes between the Czech and Dutch millennials, in order to get crucial information that is necessary for a better market orientation and development to ultimately further expand the healthy foods industry. For the purpose of this study, a survey was conducted among 344 millennials in the Czech Republic and the Netherlands. The Dutch millennials were found to consume healthy foods on a higher level than Czech millennials. Furthermore, also the gender is found to significantly influence healthy foods consumption. One of the key aspects for success in the healthy foods industry is to communicate the perceived health benefits. These benefits slightly differ for Czech and Dutch millennials. Besides that, the industry is generally lacking in triggering emotional appeals in the marketing communication. By applying the recommendations following from the results of this paper, better strategical and tactical marketing decisions can be made in order to accomplish a movement of change towards more healthy foods consumption.